Analysis of uplink user capacity for a TDD-CDMA system with a single traffic - WANG Jun-bo; CHEN Ming (Tongxin xuebao)
The uplink user capacity for a TDD-CDMA system with a single traffic was analyzed.The analysis results have a great academic significance.By taking account of the effects by the smart antenna,the joint detection,the imperfect power control,the user distribution density and timeslot allocation,a SIR model for a TDD-CDMA system,and presents a calculation method of uplink user capacity with this model and the Gaussian approximation method.Compared with the existing methods,the factors considered are more complete,so the proposed method can be used for the analysis of uplink capacity in a TDD-CDMA system under all kinds of complicated network situations.